Solidarity Stories : An Oral History of the ILWU - Schwartz, Harvey (Book collections on Project MUSE., 2009)
The International Longshore and Warehouse Union, born out of the 1934 West Coast maritime and San Francisco general strikes under the leadership of Harry Bridges, has been known for its commitment to democracy, solidarity, and social justice. In this collection of narratives, union leaders and rank-and-file workers talk about their lives at work, on the picket line, and in the union.